Parameters affecting the X-ray dose absorbed by macromolecular crystals - Murray, James W (Journal of synchrotron radiation, 2005)
The lifetime of a macromolecular crystal in an X-ray beam is assumed to be limited by the absorbed dose. This dose, expressed in Gray (Gy = J kg(-1)), is a function of a number of parameters: the absorption coefficients of the constituent atoms of the crystal, the number of molecules per asymmetric unit, the beam energy, flux, size and profile, the crystal size, and the total irradiation time. The effects of these variables on the predicted absorbed dose, calculated using the program RADDOSE, are discussed and are illustrated with reference to the irradiation of a selenomethionine protein crystal of unknown structure. The results of RADDOSE can and will in the future be used to inform the data collection procedure as it sets a theoretical upper limit on the total exposure time at a certain X-ray source. However, as illustrated with an example for which the experimental data are compared with prediction, the actual lifetime of a crystal could become shorter in those cases where specific damage breaks down crucial crystal contacts